A Training Scheme for College Communicative Teaching - Ong, Charito G. (JPAIR Multidisciplinary Research, 2009)
This study sought to design and try out a training scheme for college teachers on communicative teaching. Based on needs analysis, the teachers of English were reoriented so that they will be equipped with the rationale, strategies and assessment techniques of communicative language teaching through the six learning segments which were revised and finalized after a three-day try out. The researcher used five stages in the model to undertake the study. Specifically, the study determined: (1) the stages in the development of the training scheme and (2) the contents of the training scheme's learning segments as a product of the research. The scheme produced in this research ensures that teachers will incorporate tasks involving communication such as requiring students to do something in the lesson, with the language, or with each other. Developing students' oral and written communication skills is one of the most important goals in language teaching. These skills are essential for interactive survival in a global setting. With the use of communicative teaching techniques that are contained in the learning segments of the training scheme, these professors can provide interaction that will be meaningful, interactive, and responsive to the learners' needs as they teach minor English courses.
Keywords: communicative teaching; college teachers; training scheme